The Relationship between Nutritional Status and Learning Pattern with Learning Outcomes of Biology Student of Universitas Negeri Semarang - Nadhifah, Shiliya Lana; Yuniastuti, Ari; Pukan, Krispinus Kedati (Journal of Biology Education, 2018)
One of the indicators to measure college students’ achievement is Grade Point Average (GPA). Moreover, nutritional status and learning pattern also influence the learning outcomes. This study aimed to analyze the relationship between nutritional status and learning pattern with learning outcomes of Biology student of Universitas Negeri Semarang. The research was a mixed method research design particularly sequential explanatory strategy.The population of the research were students majoring in biology class registered as college students in 2012, 2013, 2014, 2015 and 2016. The sampling technique in the quantitative method used proportional random sampling while purposive sampling was applied in the qualitative method. Students’ learning outcomes, in this case, were GPA. Four methods in the data collection were employed. They were an assessment of Body Mass Index (BMI), questionnaires, interviews, and documentation. Data were analyzed used partial correlation analysis followed by a multiple correlation and regression analysis. The results showed that there was a positive and significant relationship as many as 44.2% of nutritional status and learning pattern with learning outcomes. Thus, it was suggested that the nutritional status and learning pattern contribute positively to improve students’ learning outcomes.